Chapter Viaggi, tempi e mondi: l'Oriente nell'opera di Mário Cláudio - Dias Nunes de Almeida, Ana Catarina (Studi e saggi, 2021)
The starting point of this paper is three works of the contemporary Portuguese writer Mário Cláudio - the novels Peregrinação de Barnabé das Índias (1998), Os Naufrágios de Camões (2017) and the play A Ilha de Oriente (1989) -, focusing on how the author rewrites the voyages of Discovery of the 16th century and shapes an image of the East. My aim is to analyse the representation of the so-called Orient and the memory of maritime travels, not only from the point of view of Mário Cláudio's poetics, but also in the light of a collective discourse that is at the same time aesthetic, historical and mythical.